Is the Earth flat or is it a cube? European foreign aid, political conditionality and democracy - Jörg Faust (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Whether political conditionality should be attached to foreign aid and whether a recipient country's level of democracy should be the benchmark for conditionality and sanctioning instruments remain highly controversial issues. This is reflected by the debates around the Agenda for Change, the allocation formula of the European Development Fund (EDF) and the European Commission's new Budget Support Policy. Critics of political conditionality argue that democracy and human rights are too normative criteria and foster the politicisation of aid allocation instead of increasing aid effectiveness. They also claim that the level of democracy is unsuitable as a criterion, because it has no influence on economic development. However, this critique can be contested: – From a perspective of domestic donor politics, democratic donor governments will not abstain from using political conditionality because their own constituencies expect human rights standards and democracy to be relevant for aid allocation. – From a recipient perspective, aid is more effective in promoting inclusive development in democracies than in autocracies. Moreover, governmental foreign aid to autocracies tends to stabilise authoritarian structures and to delay democratisation. Thus, arguing that there is little reason for using political conditionality (and sanctions) is as valid as saying that the Earth is flat. At the same time, inferring from this insight that political conditionality is bound to be effective is like claiming that the planet is a cube. After all, even sound arguments in support of political conditionality have to address the demanding challenges to make conditionality work. – The function of political conditionality must be clear. Is it used as a selection criterion, intended to ensure that foreign aid does not stabilise authoritarian structures and effectively promotes economic development? Or is political conditionality to be used in a more demanding way as an incentive to promote democracy and good governance? – If political conditionality is to be applied more proactively to promote democratic governance, donor harmonisation is key, because only a coherent incentive system sets credible signals and has a chance to contribute to institutional reform. – Effective political conditionality requires smart application. Comprehensive political reforms cannot be “bought” with foreign aid. Yet, realistic, tailor-made and credibly communicated incentives increase the probability of strengthening reform-minded forces and fostering gradual reform steps. While political conditionality has been implemented effectively in some cases, successfully applying it often overstretches the political capacities of donor coordination. For Europe, this means that effective conditionality requires a more integrated approach to foreign and development policy. – Consequently, conditionality and sanctioning instruments from policy fields such as aid, trade and investment have to be combined in an intelligent manner. Otherwise, we will continue to observe ad hoc, overly ambitious and ill-coordinated political conditionality that fails to serve its purpose.
Keywords: 330